Biotechnologies and development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Biotechnologies and development Sasson, Albert 1988 - UNESCO/CTA 360 pp. ISBN 92-3-102426-4